Technology and Aging: An Emerging Research and Development Sector in Maine - Kim, Carol; Neivandt, David; Kaye, Lenard; Crittenden, Jennifer (Maine Policy Review, 2015)
The authors discuss the importance of research for developing products and services that cater to the needs of a rapidly growing aging population and provide examples of projects underway at the University of Maine. Products designed to improve and protect older adult health and well-being represent a significant opportunity for economic growth in Maine.
Keywords: aging; technologies; Maine; research and development